Diversity and Effect of Increasing Temperature on the Activity of Methanotrophs in Sediments of Fildes Peninsula Freshwater Lakes, King George Island, Antarctica - Roldán, Diego M.; Carrizo, Daniel; Sánchez-García, Laura; Menes, Rodolfo Javier (Frontiers in Microbiology, 2022)
Global warming has a strong impact on polar regions. Particularly, the Antarctic Peninsula and nearby islands have experienced a marked warming trend in the past 50 years. Therefore, higher methane (CH4) emissions from this area could be expected in the future. Since mitigation of these emissions can be carried out by microbial oxidation, understanding this biological process is crucial since to our knowledge, no related studies have been performed in this area before. In this work, the aerobic CH4 oxidation potential of five freshwater lake sediments of Fildes Peninsula (King George Island, South Shetland Islands) was determined with values from 0.07 to 10 μmol CH4 gdw-1 day-1 and revealed up to 100-fold increase in temperature gradients (5°C, 10°C, 15°C and 20°C). The structure and diversity of the bacterial community in the sediments were analyzed by next-generation sequencing (Illumina MiSeq) of 16S rRNA and pmoA genes. A total of 4,836 ASVs were identified being Proteobacteria, Actinobacteriota, Acidobacteriota, and Bacteroidota the most abundant phyla. The analysis of the pmoA gene identified 200 ASVs of methanotrophs, being Methylobacter Clade 2 (Type I, family Methylococcaceae) the main responsible of the aerobic CH4 oxidation. Moreover, both approaches revealed the presence of methanotrophs of the classes Gammaproteobacteria (families Methylococcaceae and Crenotrichaceae), Alphaproteobacteria (family Methylocystaceae), Verrucomicrobia (family Methylacidiphilaceae), and the candidate phylum of anaerobic methanotrophs Methylomirabilota. In addition, bacterial phospholipid fatty acids (PLFA) biomarkers were studied as a proxy for aerobic methane-oxidizing bacteria and confirmed these results. Methanotrophic bacterial diversity was significantly correlated with pH. In conclusion, our findings suggest that aerobic methanotrophs could mitigate in situ CH4 emissions in a future scenario with higher temperatures in this climate-sensitive area. This study provides new insights into the diversity of methanotrophs, as well as the influence of temperature on the CH4 oxidation potential in sediments of freshwater lakes in polar regions of the southern hemisphere.